Optimisation du management stratégique et opérationnel de ligne maritime congolaise SA, entreprise publique commerciale en république démocratique du Congo (2019-2023) - Mupier Muka, Naomie (Université de Liège, 2024)
Les entreprises publiques congolaises ont fait l'objet de réformes en juillet 2008, car elles n'atteignaient pas les objectifs qui leur avaient été assignés en termes de contribution à l'économie nationale et de réponse aux problèmes sociaux de la communauté. Certaines ont été transformées en établissements publics ou en sociétés commerciales, tandis que d'autres ont été dissoutes et liquidées. Cependant, la question de l'orientation stratégique des sociétés commerciales publiques congolaises au regard de ces objectifs reste posée. Ces entreprises mettent-elles en place les outils de management stratégique nécessaires pour les atteindre ? Cette étude visait donc à analyser l'effectivité et la performance du management stratégique dans ce secteur, ainsi que son mécanisme opérationnel, en prenant le cas de l'entreprise LMC SA. Plusieurs outils techniques ont été utilisés, notamment l'analyse documentaire et des entretiens semi-directifs. Les résultats montrent un certain déficit dans la planification stratégique de ces entreprises, notamment au niveau de la gestion des ressources humaines, matérielles et financières. Sur la base de ces constats, l'étude formule quelques recommandations managériales : • Restructuration des prérogatives de l'organe de gouvernance ; • Réévaluation du capital humain et réduction des postes en trop ; • Allocation objective des ressources financières grâce à une démarche de benchmark.
Keywords: Entreprise publique commerciale; Management stratégique; République Démocratique du Congo

التضامن الصرفي في الأوراق التجارية - قلتة, محمد الأمين; بن شاعة, براهيم (Ibn Khaldun University of Tiaret, 2024)
يعد التضامن مبدأ من مبادئ القانون التجاري، وأحد أهم الضمانات التي يعتمدها قانون الصرف من أجل حصول حامل الورقة التجارية على قيمتها عند ميعاد استحقاقها، إذ يحق لهذا الأخير الرجوع على أي موقع أو على جميع الموقعين بكامل قيمة الورقة التجارية. تعد الأ وراق التجارية من وسائل الدفع التي تقوم مقام النقود في الوفاء، فهي تؤدي نفس الوظيفة التي تؤديها النقود، كما وأنها قابلة للتداول، ونظرا لأهمية هذه الأوراق في المعاملات التجارية ولكي تقوم فعلا مقام النقود في الوفاء فقد أحاطها المشرع الجزائري بمجموعة من الضمانات حماية للثقة والائتمان القائم بين التجار،ويعتبر التضامن الصرفي من أهم هذه الضمانات؛ إذ يحمي حامل الورقة التجارية ويشعره بالأمان والطمأنينة، والذي يجعل كل موقع عليها ضامنا للوفاء عند امتناع المسحوب عليه وبذلك يمكن للحامل الرجوع على الملتزمين الصرفيين منفردين أو مجتمعين والمطالبة بقيمة الورقة التجارية سواء كان ذلك في ميعاد استحقاقها أم قبل ذلك الميعاد، فكل موقع عليها يكون مسؤولا على وجه التضامن مع الملتزمين الآخرين Solidarity is one of the principles of commercial law, and one of the most important guarantees adopted by the exchange law in order for the holder of the commercial paper to obtain its value when it is due, as the latter has the right to recourse to any signatory or to all signatories for the full value of the commercial paper. Commercial papers are considered a means of payment that takes the place of money in fulfillment. They perform the same function that money performs, and they are also negotiable. Given the importance of these papers in commercial transactions, and in order for them to actually take the place of money in fulfillment, the Algerian legislator has surrounded them with a set of guarantees to protect trust and credit. existing between merchants, and exchange solidarity is considered one of the most important of these guarantees. It protects the holder of the commercial paper and makes him feel safe and reassured, which makes every signatory of it a guarantor of payment in the event of the drawee’s refusal. Thus, the holder can return to the exchange obligors individually or jointly and claim the value of the commercial paper, whether that is on its maturity date or before that date. Each signatory of it is responsible. In solidarity with other committed people.
Accepted: 2025-01-26T13:11:52Z

Le statut juridique du marchand en droit camerounais et en droit québécois - Akoumou Ndjomo, Jeanne Laure (Université de Montréal, 2023)
Ce mémoire analyse la place juridique du marchand dans les sociétés camerounaise et québécoise. Le droit a toujours cherché à catalyser les activités des marchands en régulant l’accès à leur profession, en contrôlant leurs activités et en leur imposant de nombreuses obligations. La préoccupation des législateurs québécois et camerounais vis-à-vis de l’entité qu’est le marchand est palpable, les nombreuses lois mises sur pied pour encadrer ce personnage en témoignent. Le droit camerounais et le droit québécois abordent le sujet du marchand de façon différente. Nous verrons que dans l’appellation et dans le régime applicable à cette entité, le législateur québécois et son homologue camerounais se retrouvent la majorité du temps aux antipodes l’un de l’autre, mais il arrive parfois que leurs règles présentent des similitudes. Les nombreuses règles mises en place par les législateurs pour réguler les actions du marchand vont nous amener à examiner l’importance que ce dernier a au sein de la société. Conscients du pouvoir que le marchand peut avoir, les législateurs n’ont-ils pas fixé un grand nombre de règles par peur que ce dernier abuse de ce pouvoir ? Cette interrogation nous mènera au dernier volet de ce mémoire qui consistera à analyser les rapports de forces entre le marchand et les consommateurs premièrement, et entre le marchand et l’État en seconde place. L’intérêt de cette recherche est en premier lieu juridique évidemment. En effet, au cours de notre étude, nous verrons des notions telles que la commercialité et ses éléments constitutifs et nous ouvrirons le débat sur son utilité et sa désuétude. Nous aborderons également le rôle joué par le commerçant dans le processus de globalisation du droit et la création d’un droit post-moderne. En plus d’avoir un intérêt juridique, ce sujet révèle également un intérêt socio-économique car il nous amènera à aborder la notion de « commerçant de fait », une entité apparue à cause de la précarité économique et sociale à laquelle la majorité des pays africains fait face. This study analyzes the legal place of the merchant in Cameroonian and Quebec societies. The law has always sought to catalyze the activities of merchants by regulating access to their profession, controlling their activities and imposing numerous obligations on them. The concern of Quebecer and Cameroonian legislators concerning the merchant is palpable, the large number of laws put in place to regulate this character testify to it. Cameroonian law and Quebec law approach the subject of the merchant in different ways. We will see that in the calling and in the regime applicable to this entity, the Quebecer legislator and its Cameroonian counterpart find themselves most of the time at opposite ends, but sometimes it happens that their rules present similarities. The rules put in place by legislators to regulate the actions of the merchant will lead us to examine the importance that the latter has within society. Aware of the power that the merchant can have, haven't the legislators set a large number of rules for fear that the latter will abuse this power? This question will lead us to the last part of this study which will consist in analyzing the balance of power between the merchant and the consumers first, and between the merchant and the State in second place. The interest of this research is obviously primarily legal. Indeed, during our study, we will see notions such as commerciality and its constituent elements and we will open the debate on its usefulness and its obsolescence. We will also discuss the role played by the merchant in the process of globalization of law and the creation of post-modern law. In addition to having a legal interest, this subject also reveals a socio-economic interest because it will lead us to approach the notion of "commerçant de fait", an entity that appeared because of the economic and social precariousness to which the majority of Africans countries faces.
Keywords: Cameroonian law; Commerçant; Consommateur; Consumer; Corporate Social Responsibility; Droit camerounais; Droit post-moderne; Droit québécois; Globalisation du droit; Globalization of law; Marchand; Merchant; Notion d'entreprise; Notion of enterprise; Post-modern law; Quebec law; Responsabilité sociale des entreprises; Theory of commerciality; Théorie de la commercialité; Trader

Les baux commerciaux à l'épreuve des circonstances exceptionnelles : cas du covid-19 - Ayinon, Alida (Université Grenoble Alpes, 2023)
Notre étude consistera à explorer les différents mécanismes à envisager par les locataires pour faire face à leur obligation de paiement des loyers commerciaux pendant la crise, partant bien sûr du droit covid-1911au droit traditionnel ou existant avant ladite crise. Il est à noter ici que les mesures prises par le gouvernement français dans la gestion de la crise n’ont pas eu pour vocation dans la majorité des cas de se substituer au droit existant, tel est le cas du droit des contrats. Les deux régimes étant complémentaires, en absence de réponse de l’un, l’on peut se tourner vers l’autre. Il convient de rappeler également qu’une analyse théorique ou générale du régime du bail commercial ne sera pas nécessaire car l’objectif poursuivi par ce sujet est d’examiner la règlementation législative, jurisprudentielle voire doctrinale en matière de bail commercial pendant la crise sanitaire afin de cerner leurs enjeux sur le paiement des loyers commerciaux.
Keywords: Baux commerciaux; COVID-19; Droit des affaires

Les contrats de partenariats Public-Privé, un succès rapide dissimulant beaucoup de risques : le cas de l'aéroport international Blaise Diagne de Dakar - Badji, Henry Michel Kader (Université de Liège, 2022)
Le continent Africain, un territoire avec un grand potentiel ! Près de la moitié des 20 pays à la croissance la plus rapide au monde au cours des cinq dernières années sont localisés en Afrique. Les investisseurs sont attirés par, le coût faible de la main d’œuvre, la stabilité socio-politique mais aussi et surtout par le potentiel que représente l'urbanisation et l'importance croissante de la classe moyenne. Cependant, cette croissance économique pourrait être freinée par le manque d'infrastructures du continent (routes, voies ferroviaire, ports, hôpitaux de dernière génération etc.…). Les besoins en infrastructures en Afrique subsaharienne sont estimés à plus de 93 milliards de dollars par an au cours de la prochaine décennie, et seule la moitié est disponible aujourd’hui. Les partenariats public-privé (PPP) sont donc apparus comme une alternative pour ce déficit de financement constaté. Au Sénégal, le peu de projets financés jusqu’ici avec le modèle PPP ont suscité d’énorme débats publics. La population se pose beaucoup de questions sur les avantages et inconvénients de ce type de marché. Mais à ces différentes questions, le gouvernement apporte rarement de réponses persuasives. Notre étude de recherche se veut donc, d’identifier à travers la littérature sur les PPP, mais aussi en nous appuyant sur l’analyse d’un grand projet de construction d’un aéroport, exécuté au Sénégal sous le modèle PPP, l’ensemble des risques rattachés à ce type de contrat. Le but étant de proposer à la fin de l’étude, un outil de gestion et d’anticipation sur ces risques.
Keywords: Afrique; Gestion des risques; PPP; Partenariats Public-Privé; Sénégal

النظام القانون للمؤسسات الناشئة في الجزائر - وناس, علي (Ibn Khaldun University of Tiaret, 2022)
الغاية من هذه الدراسة هو تسليط الضوء على المقاولاتية في مجال المال و الأعمال في عصرنة للنشاط التجاري بكل ركائزه منها ريادة الأعمال فظهرت المؤسسات الناشئة كخيار إستراتيجية انتهجته الجزائر و الذي فرضته العولمة و اقتصاد المعرفة المبني على تكنولوجيا المعلومات و الاتصال من أجل النهوض بالاقتصاد الوطني لتحقيق التنمية المستدامة بعيدا عن الريع. إن اهتمام الدولة بالمؤسسات الناشئة ككيان قانوني يختلف كليا عن الشركات التجارية التقليدية لأنها ترتكز على الإبداع و التكنولوجيا و سرعة النمو بأقل تكلفة، لذا خصها المشرع الجزائري بترسنة من النصوص القانونية لتحديد طبيعتها القانونية و توفير مناخ أعمال مناسب لنشاطاتها تجسدت في المرسوم التنفيذي رقم 20 - 254 المتعلق بإنشاء المؤسسات الناشئة و الحصول على علامة "مؤسسة ناشئة" و "مشروع مبتكر" و "حاضنة أعمال" و في القانون رقم 22 - 09 الذي حدد الشكل القانوني للمؤسسات الناشئة تحت عنوان "شركة المساهمة البسيطة". كما دعمها بآليات مختلفة تمثلت في صندوق خاص بتمويلها و حاضنات أعمال تسهر على تدريب فريق عملها و مرافقتها و متابعتها طيلة مراحل حياتها،إضافة إلى مزايا إعفاء جبائية. توصلت الدراسة إلى الاهتمام الكبير و الخاص بالمؤسسات الناشئة كونها الحل الاستراتيجي لتحريك عجلة التنمية الاقتصادية و تحقيق القيمة المضافة في الجزائر وضمان نجاحها. The purpose of this study is to shed light on entrepreneurship in the field of money and business in the modernization of commercial activity with all its pillars, including entrepreneurship. The emerging enterprises appeared as a strategic option adopted by Algeria, which was imposed by globalization and the knowledge economy based on information and communication technology in order to advance the national economy to achieve development sustainable without rent. The state’s interest in emerging enterprises as a legal entity is completely different from traditional commercial companies because they are based on creativity, technology and rapid growth at the lowest cost, so the Algerian legislator singled out them with an arsenal of legal texts to determine their legal nature and provide a suitable business environment for their activities embodied in Executive Decree No. 20-254 Related to the establishment of start-ups and obtaining the marks of “startup institution”, “innovative project” and “business incubator” and in Law No. 22-09 that defines the legal form of start-ups under the title “Simple Joint Stock Company”. He also supported her with various mechanisms represented in a special fund to finance her and business incubators that ensure the training of her work team, accompany her and follow up on her throughout her life, in addition to the advantages of a tax exemption. The study found a great interest in emerging institutions as a strategic solution to move the wheel of economic development and achieve added value in Algeria and ensure its success.
Keywords: Développement durable; Société par actions à responsabilité limitée; Startups; Économie de la connaissance; اقتصاد المعرفة; التنمية المستدامة; المؤسسات الناشئة; شركة المساهمة البسيطة

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)

Grupos de Sociedades Comerciais à Luz do Direito Angolano - Matias, Marlene Patrícia Fernandes (Universidade de Lisboa, 2021)
O presente trabalho tem como objeto o regime especial dos grupos de sociedades comerciais à luz do direito angolano. O principal objetivo é dar o nosso contributo para a estrutura académica do país, para um melhor conhecimento do regime, da sua grande dimensão e aplicabilidade. Dada a possibilidade de ser benéfico para diversas áreas que envolvem o regime dos grupos de sociedades. Numa época em que o país está passar por uma crise económica e sofre uma grande restruturação, o conhecimento desse regime especial é importante, não apenas para a parte académica como para muitos empresários conhecerem outros regimes societários alternativos e dinâmicos com uma outra perspetiva. Tendo uma abordagem expansiva e o conhecimento não apenas do regime angolano como dos outros países que fazem parte da comunidade lusófona. Por fim, terminamos o trabalho com a apresentação de algumas soluções e propostas compostas por um leque diversificado devido à falta de atenção por parte das instituições públicas e conhecimento dentro do sector académico.
Keywords: Angola; Direito comercial; Grupos de sociedades; Regime especial; Sociedades comerciais

جرائم الغش التجاري الواقعة على المستهلك - لوالي, خالد; معاشي, أسماء (Ibn Khaldun University of Tiaret, 2021)
يعتبر الغش التجاري من أبرز الظواهر السلبية وأكثرها انتشارا في المجتمع، ولا يكاد يخلوأي تشريع من تجريم هذه الظاهرة، التي أصابت المستهلك في مأكله ومشربه وملبسه وأغلب متطلبات حياته الضرورية منها والكمالية، ومع تقدم أساليب الإنتاج والتصنيع تطورت أساليب ووسائل الغش والتحايل على المستهلكين من قبل المتدخلين في العملية الاستهلاكية. والمشرع الجزائري على غرار التشريعات المقارنة رصد جملة من القوانين وعلى رأسها قانون العقوبات وقانون حماية المستهلك وقمع الغش لحماية المستهلك حماية موضوعية من خلال تجريمه للخداع والغش و كذا حيازة مواد مغشوشة دون مبرر شرعي، وحماية إجرائية تتمثل في استحداث هيئات رقابية منها ما هي مركزية ومنها ما هي محلية لقمع الغش التجاري، كما خول المشرع الجزائري للقضاء صلاحية متابعة جرائم الغش التجاري وفق إجراءات خاصة بدءا بتحريك الدعوى العمومية مرورا بمحاضر الشرطة القضائية ومحاضر الجهات المكلفة بحماية المستهلك، انتهاء بمرحلتي التحقيق والحكم. Commercial fraud is one of the most important and prevalent negative phenomena in society, and hardly any legislation is exempt from criminalizing this phenomenon, which has plagued consumers in their food, drink, clothing and clothing. most of the necessary and luxury needs of his life. in the process of consumption. The Algerian legislator, like the comparative legislation, controls a certain number of laws, foremost among which the Penal Code, the Law on the protection of the consumer, and the repression of the fraud to protect the consumer objectively by criminalizing the deception and fraud, as well as possession of fraudulent products. materials without legal justification, and procedural protection represented in the creation of control bodies, some of which are central and others It is local to suppress commercial fraud The Algerian legislator has also empowered the judiciary to prosecute fraud offenses commercial according to special procedures, starting with the opening of the public case, passing through the records of the judicial police and the archives of the bodies responsible for consumer protection, ending with the phases of investigation and judgment
Keywords: Droit de la consommation

E-commerce et la protection des données à caractère personnel dans l'espace OHADA - Belo Badekula, Glodi (Université Catholique de Louvain, 2021)
Face à la montée des technologies de l’information, les préoccupations en ce qui concerne la vie privée et la protection des données à caractère personnel ont émergé au sein de l’opinion publique. Plusieurs Etats avisés ont adopté des règles juridiques pour encadrer l’usage des données personnelles. Aux vues de l’importance que revêt la question de la gestion et de la protection des données à caractère personnel, et face au flux d’échanges économiques qui ont lieu dans les plateformes digitales et qui mettent en jeu les usagers et les opérateurs privés africains de la communauté OHADA, nous avons exprimé la nécessité d’examiner la problématique du « E-commerce et la protection des données à caractère personnel dans l’espace OHADA ». Il s’est agi dans le cadre de ce travail de comprendre, Comment les actes uniformes de l’OHADA protègent et préviennent la gestion abusive des données à caractère personnel, des ressortissants de l’espace OHADA à des fins économiques d’une part ; et de savoir en l’absence d’un Acte uniforme général sur la protection des données (AUGPD), quelle juridiction africaine serait matériellement compétente pour gérer des infractions liées à l’exploitation abusive des données à caractère personnel des ressortissants de l’espace OHADA, d’autre part. A l’issue de cette recherche, fort est le regret de constater que l’OHADA ne dispose jusqu’à ces jours d’aucun instrument sur la protection des données à caractère personnel et la libre circulation des données.
Keywords: Données personnelles; E-commerce; GDPR; OHADA; RGDP

Le secret dans la vie des affaires - Montrozier, Charlotte (Institut National Universitaire Champollion, 2020)
L’objet de ce mémoire de recherche dans le cadre du Master 1 Droit de l’entreprise à l’INU Champollion est de s’intéresser au « secret dans la vie des affaires ». Ce mémoire fait découvrir la notion de secret des affaires, notion prétorienne à son origine, qui n’était alors pas réglementée par le droit français. Cette problématique de consécration a fait l’objet de longs débats. Par la suite, cette notion de secret des affaires a fait l’objet d’une consécration européenne puis interne par la transposition de la directive par la loi du 30 juillet 2018. Désormais, le secret des affaires est défini à l’article L.151-1 du code de commerce. Cet événement marque alors une avancée majeure dans la protection de ce secret. Enfin, il s’est avéré judicieux de confronter la notion de secret des affaires à d’autres matières. Cette confrontation a montré que la conciliation pouvait être respectée dans son ensemble mais pas de manière absolue. La préservation est un idéal à atteindre mais celui-ci fait l’objet de tempéraments. De la sorte, il a fallu s’interroger sur la manière dont le droit interne envisage la protection du secret dans la vie des affaires. Comment un tel secret est protégé ? Qu’est ce qui a été mis en place pour garantir sa protection ? Sachant qu’un tel procédé alterne toujours entre protection et défaillance.
Keywords: Brevet; Droit d'auteur; Droit exclusif; Intellectual property; Intelligence économique; Liberté d'expression; Liberté de la presse; Propriedade intelectual; Propriété intellectuelle; Secret – Droit; Secret des affaires; Transparence de l'entreprise

The position of assets vested in a sham trust - Diedericks, C. A. (North-West University, 2018)
The concept of a sham trust has changed over the years. Presently it is defined as a perceived entity that is not entirely what it portrays to be. In addition, a sham is therefore regarded as invalid with a deceiving nature. A sham trust has the consequence that all the benefits and protection of assets are destroyed, seeing that no trust actually came into existence. Considering the above, for the purpose of the present study, only an inter vivos trust was evaluated and discussed in detail. The law of contract is considered to be the foundation of the principles for an inter vivos trust. Therefore, the law of contracts can be applied to solve problems presented by trusts. During the course of the present research, it became evident: in instances where a trust is declared a sham, the consequence is that the trust will be deemed void. There are instances where a sale agreement has been concluded prior to the discovery of the true nature of the trust, namely it being a sham. This raises the question on the legal position of assets vested in a sham trust. A further question arises about the consequences and whether the courts should set a guideline for such instances. From the findings it is evident that such a guideline is necessary. This would enable courts to determine the consequences of assets vested in a sham trust. There are various possibilities regarding consequences for assets vested in a sham trust. To determine the applicable consequence, the court should deal with each case individually based on the facts of that particular circumstances. This consequence could either entail that the assets should fall within the founder’s personal estate, or whether the concluded sale agreement should be deemed void. It is evident that the courts struggled with the distinction between a sham and alter ego trust, however, the case law referred to below gives more clarity in this regard. A proper formulation of the aspects of sham and alter ego trusts was provided in the cases of Van Zyl v Kaye1 and Van der Merwe v Hydraulics.2 The formulation of the two aspects in the above-mentioned cases was confirmed in the Supreme Court of Appeal judgement in the case of WT v KT.3 In the Khabola v Ralitabo,4 the court dealt with the typical example of the sham trust. In brief, the fact of the case were, that the parties had the intention to establish a partnership that was simulated to be a trust.
Boloka Institutional Repository https://repository.nwu.ac.za/handle/10394/31321
Keywords: Assets; Contract of sale; Intention; Law of contract; Legal position; Sham trust; Snook test; inter vivos trust

L'équilibre contractuel - Muggeo, Marine-Alice (Université de Toulon, 2017)
Ces dernière années, le concept d'équilibre contractuel est devenu omniprésent dans notre droit et se retrouve dans quasiment toutes les disciplines du droit. L'équilibre contractuel n'a donc eu de cesse de se renforcer (Titre 1) dans diverses disciplines, car le droit des contrats est une matière transversale. On retrouve donc cette notion autant dans les contrats spéciaux que dans le droit commun des contrats. Ainsi une fois étudié, cet équilibre se retrouve dans les différentes phases de construction et d'exécution du contrat (Titre 2). C'est une partie qu'il faut appréhender car cela nous permet de comprendre où se retrouve l'équilibre dans le contrat. Et constater que c'est une notion centrale qui se retrouve dans l'ensemble des phases pré-contractuelles et contractuelles.
Keywords: Contrats d'affaires; Contrats informatiques; Contrats spéciaux; Crédit consommation; Droit des contrats; Honoraires avocats; Sécurité juridique

L'étendue de la compétence ratione materiae du juge étatique dans le règlement des différends nés de l'exécution d'un contrat complexe - Djemba Kandjo, Joseph (Université de Montréal, 2015)
Les arrêts sur l’affaire Beaudoin c. Université de Sherbrooke (Cour Supérieure et Cour d’Appel du Québec 2008-2010) ont porté sur l’intensité de l’obligation de consultation insérée dans l’accord de partenariat de recherche. Ce type de partenariat est souvent créé par un accord et peut prendre plusieurs formes. La plupart d’entre elles sont méconnues par le droit, c’est pourquoi la doctrine les considère comme étant des entreprises complexes puisque le choix des partenaires est souvent guidé par le souci d’échapper au formalisme qu’imposent les règles étatiques. Cependant, les pratiques connues dans le secteur d’activité des associés et les accords qui les lient sont souvent les seules règles qu’ils suivent. En cas de conflit, ils recourent généralement à un tiers expert pour régler leur litige, la saisine des tribunaux ne se faisant qu’exceptionnellement. Dans cette cause, les contractions entre les deux décisions ont soulevé quelques interrogations : d’une part, sur la capacité des tribunaux à trancher des conflits qui peuvent naître au cours de l’exécution de ce type de contrat, et d’autre part sur la compatibilité des règles matérielles applicables au fond par les juges lorsque les parties ne sont liées que par la lex contractus et les usages reconnus dans leur secteur d’activité. Cette étude tente donc d’identifier la forme de partenariat en cause afin de mesurer l’étendue de la compétence ratione materiae du juge dans la résolution des conflits nés d’un contrat complexe (PARTIE I), et d’examiner l’opportunité de recourir aux modes alternatifs de résolution des litiges (PARTIE II). The decision in the case Beaudoin v. Université de Sherbrooke (Superior Court and Quebec's Court of Appeal 2008-2010) examines the extent of the obligation to consult in a research partnership agreement. This kind of partnership is often created through agreements and can take several forms. The majority of those are unknown to the law; this is why the doctrine considers them to be complex enterprises, since the choice of the partner is often guided by the will to curtail the formalism imposed by State rules. Familiar practices used in the relevant field and the agreements which link them are often the only rules they respect. In case of dispute, they generally seek a third party expert to settle the dispute and only exceptionally resort to national courts. In this specific case, the contractions present the decision raise some important questions: on one hand, the capacity of the courts to solve conflicts which arise from the execution or interpretation of this sort of partnership, and on the other hand the compatibility of material rules applicable to the subject matter by judges to parties often bound by lex contractus and the usages applicable in their field of activity. This study tries to identify the form of partnership applicable in this case in order to measure the extent of the ratione materiae competence of the judge in the settlement of a dispute arising from the execution of a complex contract (PART I), and to examine the possibility of recurring to alternative forms of dispute settlement for disputes of this nature (PART II).
https://papyrus.bib.umontreal.ca/xmlui/bitstream/handle/1866/11876/Djemba-kandjo_Joseph_2014_memoire.pdf
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrator; Arbitre; Commercial; Commerciaux; Compétence; Différend; Dispute; Joint-venture; Judge; Juge; Lex; Material; Matérielle; Mercatoria; Political Science; Usages

Acentenin ücret hakkı - Kizilay, Aygül (Kocaeli Üniversitesi, 2015)
6102 sayılı TTK acentelik alanında önemli yenilikler getirmiştir. Yeni kanun 6762 sayılı Kanunda yer almayan bazı kurumlara yer vermiş, eski kanun döneminde uygulamada sorunlara yol açan bazı hükümler ise gözden geçirilmiştir. Acentelik sözleşmesi tam iki tarafa borç yükleyen sözleşme olduğundan, acentenin gördüğü iş için her zaman bir ücret talep etme hakkı bulunmaktadır. Acentenin en önemli hakkı olan ücret hakkı, müvekkilin karşı edimi olarak kendisini gösterir. Ücret hakkını düzenleyen hükümler arasında ücrete hak kazandıran işlemler ve ücrete hak kazanma zamanı ile ilgili hükümler yeniden ele alınmıştır. Bunlarla birlikte ücret hakkıyla ilgili olarak acenteye çok geniş bir bilgi alma ve defter kayıtlarını isteme ve inceleme hakkı tanınmıştır. Çalışma "Giriş" ve "Sonuç" bölümleri haricinde üç bölümden oluşmaktadır. Birinci bölümde acente kavramı ve bu kavramı oluşturan unsurlar incelenmiştir. Ayrıca acentenin hak ve borçlarına değinilmiştir.Çalışmanın ikinci bölümünde, acentenin en temel hakkı olan ücret hakkı incelenmiş olup; üçüncü bölümde ise, 6102 sayılı TTK ile getirilen düzenlemeler ve değişiklikler, 6762 sayılı TTK ile karşılaştırmalı olarak ele alınmıştır. Ücret hakkına ilişkin bu değişiklikler, acentelik sözleşmesi sona erdikten sonra acentenin ücret talep edebileceği haller; ücrete hak kazanma anındaki ve ücretin muaccel olacağı andaki değişiklikler; ücret hakkında acentenin belge ve bilgi isteme hakkının emredici olarak düzenlenmesi olarak özetlenebilir. Law no. 6102 Turkısh Commercial Code brings advances at provisions about agency .The new Code brings new provions comparing with Law no. 6762 Turkısh Commercial Code. Furthermore, it resolves some issues existing in the period of 6762 Turkısh Commercial Code. Agency contract is a bilateral contract. Therefore the rights of the agent, constitutes theobligations of the principal. The commission right is also obligation of the principal. The provisions about commission right are reargued out, including transactions which bearing commission and time of entitlement of commission This thesis is consist of three chapters excluding the "introduction" and the "conclusion" parts. In first chapter, the notion of the agent and the elements of this notion are discussed. Moreover, rights and obligations of agent are examined. In chapter two, the principal right of agent, commission right is discussed. In chapter three, commission right is examined comparing with the provisions of Law no. 6102 Turkısh Commercial Code and Law no. 6762 Turkısh Commercial Code. Amendments about commission right are time of entitlement of commission , time of commission becoming payable. Furthermore , in some cases, an agent shall be entitled to commission on commercial transactions concluded after the agency contract has terminated. Lastly, an agent shall be entitled to demand that he be provided with all the information, and in particular an extract from the books, which is available to his principal and which he needs in order to check the amount of the commission due to him. Provision about demanding information is statutory.
433640
Keywords: Acenteler; Agents; Commissions; Kanunlar 6762 sayılı; Komisyonlar; Laws 6762 numbered; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Wage policies; Wage systems; Ücret politikaları; Ücret sistemleri

Avoidance of a contract under the CISG - Otenga, Emongo Jean-Marc (University of Johannesburg, 2015)
Keywords: CISG; Commercial law; Contracts (International law); United Nations Convention on Contracts for the International Sale of Goods (1980 April 11)

La résolution du contrat de vente en droit OHADA : d’une réforme à l’autre - Ebata, Rodrigue N. (Université de Montréal, 2014)
La présente étude examine une des difficultés que soulève la résolution du contrat de vente en droit africain des affaires. L'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) créée par le Traité du 17 octobre 1993 organise les règles communautaires relatives à la résolution du contrat de vente. Le Livre VIII de l’Acte uniforme OHADA portant sur le Droit commercial Général a été adopté le 15 décembre 2010 et a abrogé l’Acte du 17 avril 1997. Selon l’article 281 de l’Acte uniforme, la résolution du contrat de vente ne survient que lors de l’inexécution totale ou partielle de l’obligation du cocontractant. Notre étude visera à évaluer les conséquences dans le droit de la vente OHADA de la substitution du critère de privation substantielle par celui de la gravité du comportement du débiteur justifiant une résolution unilatérale du contrat. Cette nouvelle position du droit de la vente OHADA se démarque dans une certaine mesure du droit matériel uniforme et rejoint un courant adapté aux impératifs socioéconomiques du commerce tant régional qu’international. En outre la partie lésée devra déterminer la gravité du comportement du débiteur au risque de voir sa demande sanctionnée pour défaut de droit et donner lieu à des dommages intérêts à l’autre partie. En effet, avec pour optique la nécessité de sauvegarder le contrat au nom du principe favor contractus, comment le juge détermine a posteriori si la gravité du comportement du cocontractant est suffisante pour anéantir le contrat? Ce nouveau critère de la gravité du comportement du cocontractant en droit de la vente OHADA vient supplanter le critère de la privation substantielle et fait cohabiter la traditionnelle résolution judiciaire avec celle de la résolution unilatérale dont les contours demeurent incertains. Les cas d’ouvertures liés à la résolution du contrat de vente OHADA pour inexécution des obligations fondamentales ou accessoires seront passés au crible de même que leurs effets sur les parties. Dans une approche comparatiste avec la Convention de Vienne et les règles de codifications privés telles que les Principes UNIDROIT ou du Droit Européen des Contrats il y a lieu de s’interroger sur la mise en œuvre et les conséquences de la résolution du contrat de vente OHADA par l’inexécution de l’obligation d’une des parties due à un manquement essentiel d’une part et à la gravité du comportement du débiteur d’autre part. The Treaty on Harmonisation of Business Law in Africa signed on October 17th, 1993 created the Organisation for Harmonisation of Business law in Africa (OHBLA).OHBLA organises common rules on resolution of sales contracts. The Book VIII of the Uniform act on General Commercial Law adopted on December 15th, 2010 replaces the previous act of April 17th, 1997. According to article 281 of this uniform act, contract resolution only occurs when there is a partial or total non execution of one party’s obligation. The present study is going to examine one of the difficulties that exist in the resolution of sales contracts in African business law. Our study will consist in evaluating the consequences of substitution of the substantial privation criteria by the seriousness of the debtor’s behaviour in OHBLA sales law. This substitution justifies a unilateral contract termination. This new OHBLA law position somehow distinguish itself from material uniform law and joins a new position socioeconomically more adapted to regional and even international business. Moreover, the prejudiced party will have to determine the gravity of the debtor’s behaviour risking to be punished for lack of motives and according damages to the other party. In fact, in order to save the contract by all means according to the favor contractus principle, how will the judge subsequently determine if the debtor’s behaviour gravity is enough to breach the contract? This new criterion of the gravity of a contracting party’s behaviour comes in replacement of the substantial privation criteria and enhances the cohabitation of the traditional judiciary termination and the unilateral cancellation which is still uncertainly defined. Cases related to contract resolution caused by non-execution of mandatory or accessory obligations in OHBLA law will be carefully examined as well as their effects on contracting parties. In a comparative approach with the Vienna Convention and private codifications such as UNIDROIT principles or European contract law, we will wonder about the use and the consequences of resolution of sales contract in OHBLA law caused by non-execution a mandatory obligation on one part and the gravity of one party’s behaviour on the other part.
Keywords: African law; Business law; CISG; CVIM; Commerce international; Commercial law; Contract; Contrat; Contrats internationaux; Droit africain; International business; International sales; OHADA; OHBLA; Resolution; Résolution; Sales; Sales law; UNIDROIT; Vente; Vente internationale

Da admissibilidade do direito de retenção no contrato de empreitada de construção imobiliária - Correia, Armando Francisco Gonçalves (Universidade Católica Portuguesa, 2013)
Keywords: Construction immobilière; Contrat; Droit de rétention; Immeuble (construction)

O direito de retenção do empreiteiro na empreitada de construção de imóveis - Nunes, Fernando Jorge da Costa Mota (Universidade Católica Portuguesa, 2012)
Keywords: Construction immobilière; Contrat; Droit de rétention; Immeuble (construction)

Commercial law reform in Africa: a means of socio-economic development, but for whom? Perspective of women entrepreneurs in Benin - Deschamps, Isabelle (McGill University, 2011)
This thesis explores the interactions between French and foreign influenced formal commercial law in the Republic of Benin and women's on-the-ground business practices. It uses a comparative, historical and inter-disciplinary and empirical methodology (Clinical legal pluralism). It contributes to the debate on the relationship between law and socio-economic development in African States where formal law is modeled on that of their former colonizing power. The dissertation looks at the evolution of business law and of economic activity in the region from pre-colonial times to present where OHADA Uniform Acts ("Acts") largely inspired by French and foreign law constitute Beninese formal commercial law's primary source. The thesis then examines elements of businesswomen's socio-cultural realities and economic practices in the region to assess the extent to which they are accounted for in formal law. The analysis reveals the considerable gap that continues to exist between the Western-inspired Acts and the realities and modes of Beninese women entrepreneurs. While the OHADA regime may benefit French and other foreign companies that contribute to the region's economic vitality to varying extents, the difficult appropriation and access by a majority of citizens and enterprises in Benin to OHADA laws prevent Beninese (in particular female) small and medium enterprises from playing a greater role in the socio-economic development of their countries. The dissertation suggests that the paradigms and methods currently used by OHADA and international organizations such as the World Bank in their law reform activities do not take appropriate account of economic, social and cultural realities of the regions where the new law is to be implemented. These include gender issues in business practices. It argues that commercial law reformers should recognise the central role of citizens in creating the law. Finally, it outlines an analytical framework for applying these objectives so as to empower citizens in Benin as lawmakers. This framework will integrate some of existing law reform paradigms with additional ones focused on the identity of legal actors in the region (banks, small, medium and large entrepreneurs, micro-credit institutions, financiers, etc.), the dynamics between them, the role of women in business and alternative legal reform methods based on bottom-up approaches to law. Ce mémoire s'intéresse aux interactions entre le droit commercial d'inspiration française ou étrangère dans la République du Bénin avec les réalités pratiques que les femmes commerçantes y vivent sur le terrain. Une méthodologie comparative, historique et interdisciplinaire y est employée (pluralisme juridique clinique). Il se veut une contribution au débat sur la relation entre le droit et le développement socio-économique dans les États Africains où le droit formel prend modèle sur celui de leur ancienne métropole.L'auteure débute en examinant l'évolution du droit des affaires et de l'activité économique dans la région à partir de l'époque précoloniale jusqu'à aujourd'hui, où les Actes Uniformes OHADA (les « Actes »), fondés largement sur le droit Français et étranger, constituent la source la plus importante du droit commercial Béninois.Elle poursuit en explorant les réalités socioculturelles et les pratiques économiques des femmes commerçantes dans la région afin de vérifier dans quelle mesure elles sont prises en compte par le droit formel. Cette analyse révèle un écart considérable qui perdure entre les Actes d'inspiration occidentale et les réalités et pratiques des femmes commerçantes Béninoises.Bien que le régime OHADA puisse bénéficier aux investisseurs Français et étrangers qui contribuent, à divers degrés, à l'activité économique dans la région, la difficulté pour une majorité de citoyens et d'entreprises Béninois à s'approprier ou accéder aux Actes empêchent les petites et moyennes entreprises Béninoises (particulièrement celles dirigées par des femmes) de jouer un plus grand rôle dans le développement socioéconomique de leur pays.L'auteure postule que les paradigmes et méthodes employés par l'OHADA ainsi que par des organisations internationales telles la Banque Mondiale dans le cadre de leurs activités de réforme législative ne tiennent pas suffisamment compte des réalités économiques, sociales et culturelles des régions où leurs réformes sont mises en œuvre. Ces réalités comprennent les questions liées au genre dans le cadre des pratiques commerciales. L'auteure suggère que les réformateurs du droit commercial reconnaissent davantage le rôle central que les citoyens jouent dans la création du droit.Enfin, le mémoire trace les contours d'un cadre analytique qui applique ces objectifs de façon à réhabiliter les citoyens Béninois à titre de créateurs de droit. Ce cadre intègre quelques-uns des paradigmes existants sur la réforme du droit avec de nouveaux paradigmes centrés sur l'identité des acteurs juridiques dans la région (les banques, les petites, moyennes et grandes entreprises, les institutions de microcrédit, les investisseurs, etc.), les dynamiques entre eux, le rôle des femmes dans le milieu des affaires et les méthodes alternatives de réforme législative fondées sur une approche juridique du bas vers le haut.

La preuve et la conservation de l'écrit dans la société de l'information - Caïdi, Stéphane (Université de Montréal, 2002)
Il est devenu commun de dire que notre société se transforme inexorablement en une société dite de « l'information ». Cette transformation se caractérise entre autres par une utilisation accrue des technologies de l’information afin de communiquer, d’échanger ou de transiger. Les supports traditionnels de communication (tel que le papier) cèdent progressivement leur place à de nouveaux supports technologiques favorisant l’efficacité et la rapidité des échanges, et par la même occasion le développement du commerce électronique. Qu’on le souhaite ou non, un constat s’impose : la montée en puissance des réseaux virtuels a eu raison du monopole du papier. Sur le plan juridique, cette nouvelle réalité bouleverse aussi considérablement les règles de droit civil largement pensées et ancrées dans un contexte papier. L’avènement de la numérisation et du phénomène de la dématérialisation des supports ont effectivement soulevé plusieurs questions d’ordre juridique tout à fait nouvelles que nous pourrions résumer de la manière suivante : Quels sont les rapports entre l’écrit et son support autre que le papier? Quelles sont les caractéristiques de l’écrit faisant appel aux technologies de l’information? Ce type d’écrit peut-il être admis en tant que moyen de preuve? Si oui, quelle sera sa force probante? Ce type d’écrit doit-il être conservé? Le présent mémoire vise précisément à identifier certains éléments de réponses à ces diverses questions en étudiant spécifiquement les cadres juridiques français et québécois. Ce mémoire traite d’une part des enjeux liés à l’évolution et au rôle de l’écrit face à l’avènement des technologies de l’information et d’autre part du cadre juridique de la preuve et de la conservation de l’écrit dans la société de l’information.
Keywords: Archivage; Archives; Communication formats; Evidence; Information and communication technologies; Preuve; Support; Technologies de l'information; Writing; Écrit